Global strategies to reduce the price of antiretroviral medicines: evidence from transactional databases - Brenda Waning; Warren Kaplan; Alexis C King; Danielle A Lawrence; Hubert G Leufkens; Matthew P Fox (The World Health Organization, 2009)
OBJECTIVE: To estimate the impact of global strategies, such as pooled procurement arrangements, third-party price negotiation and differential pricing, on reducing the price of antiretrovirals (ARVs), which currently hinders universal access to HIV/AIDS treatment. METHODS: We estimated the impact of global strategies to reduce ARV prices using data on 7253 procurement transactions (July 2002-October 2007) from databases hosted by WHO and the Global Fund to Fight AIDS, Tuberculosis and Malaria. FINDINGS: For 19 of 24 ARV dosage forms, we detected no association between price and volume purchased. For the other five ARVs, high-volume purchases were 4-21% less expensive than medium- or low-volume purchases. Nine of 13 generic ARVs were priced 6-36% lower when purchased under the Clinton Foundation HIV/AIDS Initiative (CHAI). Fifteen of 18 branded ARVs were priced 23-498% higher for differentially priced purchases compared with non-CHAI generic purchases. However, two branded, differentially priced ARVs were priced 63% and 73% lower, respectively, than generic non-CHAI equivalents. CONCLUSION: Large purchase volumes did not necessarily result in lower ARV prices. Although current plans for pooled procurement will further increase purchase volumes, savings are uncertain and should be balanced against programmatic costs. Third-party negotiation by CHAI resulted in lower generic ARV prices. Generics were less expensive than differentially priced branded ARVs, except where little generic competition exists. Alternative strategies for reducing ARV prices, such as streamlining financial management systems, improving demand forecasting and removing barriers to generics, should be explored.